Productivity, compatibility and economics of wheat (Triticum aestivum) and Indian mustard (Brassica juncea) intercropping as influenced by farmyard manure and fertilizer levels under irrigated conditions - SINGH, RAJESH KUMAR; SINGH, UMENDRA; MEENA, RAMAWATER (The Indian Journal of Agricultural Sciences, 2018)
A field experiment was conducted during winter (rabi) seasons of 2010-11 and 2011-12 at Institute of Agricultural Sciences, Banaras Hindu University, Varanasi to evaluate the productivity, compatibility and economics of wheat (Triticum aestivum L.) and Indian mustard (Brassica jancea) intercropping as influenced by row proportions, farmyard manure (FYM) and fertilizer levels under irrigated conditions. The experiment was laid out in three times replicated split plot design, where main-plots received four wheat + Indian mustard intercropping row proportions (8:1, 6:2, 8:2 10:2) and sub-plots got four levels of the combined application of farmyard manure (15 and 30% N) and fertilizer (75 and 100% recommended doses of fertilizer) applied on area basis. The productivity of wheat and mustard in wheat + mustard intercropping in terms of yield parameters, viz. grains/spike, spikelets/spike, 1,000-grain weight and seed yield as well as straw yield in wheat, and siliquae/plant and seeds/siliqua of Indian mustard, were significantly higher with row proportion of 8:1 over 10:2, 8:2 and 6:2. However, seed yield and stover yield of Indian mustard was higher in 6:2 row proportion which was at par with 8:2 and 10:2 row proportions. Wheat + Indian mustard intercropping under 10:2 row proportion proved more remunerative and recorded higher yield advantage than 8:1, 8:2 and 6:2 row proportions as judged by total land equivalent ratio, monetary advantage, net return and benefit: cost ratio. The aggressivity was higher for Indian mustard than wheat. Application of 15% or 30% N through FYM + 100% recommended doses of fertilizer (RDF) significantly enhanced yield attributes and yield of wheat and Indian mustard. The highest total land equivalent ratio and aggressivity of Indian mustard indicated superiority of the application of 30% N through FYM + 100% RDF. However, benefit: cost ratio was highest in the application of 15 kg N through FYM +100% RDF.